Beban Kognitif Mahasiswa dalam Penyelesaian Soal Model Kreatif Pada Materi Teori Graf - Saesar Adhe Prambudi; Barep Yohanes; Nazalia Rahma; Lailatul Fitria; Husnul Khotima (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
This study aims to analyze students' cognitive load in solving creative problems of imitation, modification, and creation types on graphs. The study used a qualitative approach with a case study design involving three students in the Mathematics Education Study Program. Data were obtained through creative problem tests and interviews based on cognitive load indicators, then analyzed based on the relationship between thought processes and the types of cognitive load that emerged. This study refers to the latest developments in Cognitive Load Theory, which distinguishes cognitive load into intrinsic and extraneous, and views germane processing as a productive cognitive activity. The results show that each creative stage has distinct cognitive load characteristics. At the imitation stage, students exhibited relatively low cognitive load. The modification stage was the most critical stage due to the increased cognitive load resulting from the complexity of concept integration. Meanwhile, at the creation stage, students who were able to manage cognitive load demonstrated the dominance of germane processing in generating new solutions. These findings emphasize the importance of managing cognitive load in creative learning through gradual support, such as scaffolding. Future research is recommended to examine scaffolding strategies and combine qualitative and quantitative approaches.Keyword: cognitive load, creative thinking, imitation, modification, creation, graph theory